A Role in Migration for the αvβ1 Integrin Expressed on Oligodendrocyte Precursors - Milner, Richard (J Neurosci, 1996)
Myelination of the CNS requires the migration of oligodendrocyte precursors throughout the CNS from restricted regions within the ventricular and subventricular zones. In light of the significant effects of cell–extracellular matrix (ECM) interactions on cell migration in other developing systems, we have analyzed the role of integrins in oligodendrocyte precursor migration. We have shown previously that oligodendrocyte precursors in vitroexpress a limited repertoire of integrins, including α6β1, αvβ1, and αvβ3, and that differentiation is associated with downregulation of αvβ1 and upregulation of αvβ5. Using a migration assay based on the movement of cells away from an agarose drop containing a high-density cell suspension, we find that RGD peptides (that block αv but not α6 integrins) and anti-β1 antibodies block migration on an astrocyte-derived ECM, whereas anti-β3 antibodies have little effect. These re- sults suggest that αvβ1 but not α6β1 plays a role in oligodendrocyte precursor migration, and this is confirmed by the use of blocking monoclonal antibodies that distinguish these two integrins. In keeping with the results of others, we find that differentiated oligodendrocytes lose migratory potential and that the timing of this loss correlates with downregulation of αvβ1. Taken together with the work of others showing that ECM ligands for αvβ1 are expressed within the CNS, we propose that this integrin plays a significant role in the migration of oligodendrocyte precursors in vivoand that its downregulation during differentiation could be an important factor regulating the migratory phenotype of these cells.